Design and development of smart list: a mobile app for creating and managing grocery lists - Katuk, Norliza; Jayasangar, Tamilarasi; Yusof, Yuhanis (2019)
Research in consumer science has proven that grocery shopping is a complex and distressing process. Further, the task of generating the grocery lists for the grocery shopping is always undervalued as the effort and time took to create and manage the grocery lists are unseen and unrecognized. Even though grocery lists represent consumers’ purchase intention, research pertaining the grocery lists does not get much attention from researchers; therefore, limited studies about the topic are found in the literature. Hence, this study aims at bridging the gap by designing and developing a mobile app (application) for creating and managing grocery lists using modern smartphones. Smartphones are pervasive and become a necessity for everyone today. Hence, a smartphone app that can facilitate the process of creating and managing grocery lists for busy and working people is beneficial. The design and development of the app followed the rapid application development methodology. First, the functional requirements were gathered through interviews and content analysis. Then, a prototype named SMART LIST has been developed based on the gathered requirements, and a field study was carried out to evaluate the usability of the prototype. The results of the evaluation suggested that SMART LIST is useful and easy to use. The respondents also satisfied with the functions for managing grocery lists offered by SMART LIST. The study contributes towards an understanding the system requirements and user interface of a mobile app for managing grocery list. It can be a reference model for developers and researchers in the area to develop similar apps or enhancing the capabilities in creating and managing grocery lists. أثبت البحث في علم المستهلك أن التسوق في البقالة عملية معقدة ومحزنة. علاوة على ذلك ، يتم دائمًا تقدير مهمة إنشاء قوائم البقالة الخاصة بتسوق البقالة لأن الجهد المبذول والوقت المستغرق لإنشاء قوائم البقالة وإدارتها غير مرئي وغير معترف به. على الرغم من أن قوائم البقالة تمثل نية شراء المستهلكين، إلا أن الأبحاث المتعلقة بقوائم البقالة لا تحظى باهتمام كبير من الباحثين ؛ لذلك، توجد دراسات محدودة حول الموضوع في الأدب. وبالتالي، تهدف هذه الدراسة إلى سد الفجوة من خلال تصميم وتطوير تطبيق (تطبيق) للهاتف المحمول لإنشاء وإدارة قوائم البقالة باستخدام الهواتف الذكية الحديثة. الهواتف الذكية منتشرة وتصبح ضرورة للجميع اليوم. وبالتالي، فإن تطبيق الهاتف الذكي الذي يمكن أن يسهل عملية إنشاء وإدارة قوائم البقالة للأشخاص المشغولين والعاملين مفيد. يتبع تصميم وتطوير التطبيق منهجية تطوير التطبيق السريع. أولاً ، تم جمع المتطلبات الوظيفية من خلال المقابلات وتحليل المحتوى. بعد ذلك، تم تطوير نموذج أولي باسم SMART LIST بناءً على المتطلبات المجمعة، وتم إجراء دراسة ميدانية لتقييم قابلية استخدام النموذج الأولي. تشير نتائج التقييم إلى أن قائمة SMART LIST مفيدة وسهلة الاستخدام. راضون أيضًا عن وظائف إدارة قوائم البقالة التي تقدمها SMART LIST. تساهم الدراسة في فهم متطلبات النظام وواجهة المستخدم لتطبيق الجوال لإدارة قائمة البقالة. يمكن أن يكون نموذجًا مرجعيًا للمطورين والباحثين في المنطقة لتطوير تطبيقات مماثلة أو تعزيز القدرات في إنشاء قوائم البقالة وإدارتها.